Pergaruh Rendaman Pada Marshall Campuran AC-BC Limbah Ban Karet Bekas Sebagai Agregat Pengganti - Muhammad Ady Mulyadi; Jasman Jasman; Mustakim Mustakim (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Utilization of new technologies in asphalt mixture production includes soaking technologies that can enhance mechanical properties of the mixture. This research aims to evaluate pavement vulnerability to water and the environmental quality impact due to waste from used rubber tires as an effort to strengthen pavements by substituting asphalt. The variables studied are variations of used rubber tire waste at 0%, 2%, 3%, and 4% replacing asphalt content in AC-BC mixtures. Testing was conducted using the Marshall method by soaking the mixtures in water for normal duration, 30 minutes, 24 hours, and 72 hours. The test results indicate that higher percentages of used rubber tire waste and longer soaking durations lead to a decrease in AC-BC mixture characteristics. The Marshall value of the AC-BC mixture with 2% used rubber tire waste was found to be superior compared to mixtures with 0%, 3%, and 4%. From the data analysis conducted, it can be concluded that water has a negative influence on the Marshall value reduction of mixtures containing used rubber tire waste, correlating with increased soaking duration.